Atividade tripanocida, rendimento e composição química do óleo essencial de Piper marginatum - Oliveira, Midiã Rodrigues de (Brasil, 2019)
The specie Piper marginatum belongs to the Piperaceae family and is among the most studied of the genus Piper for its various applications in folk medicine such as tonic, carminative and antispasmodic This work aims to evaluate yield, chemical composition and trypanocidal activity of the essential oil of Piper marginatum leaves. The leaves were collected at Km 18 of the AM-010 road and the essential oils were obtained by hydrodistillation of the fresh material in a clevenger apparatus. The oils obtained from six extractions, which presented variations in their yield, were evaluated. The highest yield was obtained during the rainy season (0,20%) and the smallest during the dry season (0,11%), evidencing this way that the essential oils content of this plant is affected by variations in parameters such as temperature and pluvimetric index. The major compounds identified were: δ-3-Carene (14,87%) and trans-β-ocimene (10,92%) for the sample collected in august 2018. For the sample collected in december 2018, δ-3-Carene (10,52%) were identified and, trans-β-ocimene (9,96%), as major constituents. The oil was effective active against strains of Trypanosoma cruzi.